2002
DOI: 10.1023/a:1019693504183
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the DNA Repair Enzyme XPD are Associated with Increased Levels of PAH–DNA Adducts in a Case-Control Study of Breast Cancer

Abstract: We present findings on the associations between DNA adduct levels in breast tissue, risk of breast cancer, and polymorphisms in the DNA repair enzyme XPD. Breast cancer cases, benign breast disease (BBD) controls, and healthy controls were enrolled. Polycyclic aromatic hydrocarbons (PAH)-DNA adduct levels were measured by immunohistochemistry in breast tissue samples from cases and BBD controls. XPD polymorphisms at codons 312 and 751 was determined by polymerase chain reaction (PCR) and restriction fragment l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 38 publications
8
54
0
1
Order By: Relevance
“…In vitro studies (11)(12)(13) show that PAHs are metabolized in human breast epithelial tissue to form PAH-DNA adducts. Previous epidemiologic studies (14,15) noted that increased levels of aromatic DNA adducts in breast tissue were associated with breast cancer risk. Methods for measuring DNA adducts in humans have become more reliable in recent years, allowing detection of even background adduct levels in environmentally exposed individuals (16).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In vitro studies (11)(12)(13) show that PAHs are metabolized in human breast epithelial tissue to form PAH-DNA adducts. Previous epidemiologic studies (14,15) noted that increased levels of aromatic DNA adducts in breast tissue were associated with breast cancer risk. Methods for measuring DNA adducts in humans have become more reliable in recent years, allowing detection of even background adduct levels in environmentally exposed individuals (16).…”
Section: Introductionmentioning
confidence: 93%
“…Methods for measuring DNA adducts in humans have become more reliable in recent years, allowing detection of even background adduct levels in environmentally exposed individuals (16). PAH-DNA adduct levels reflect both exposure to PAH and possibly modulation of exposure by genetic factors, which affect carcinogen metabolism and DNA repair (15,(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have showed the polymorphisms at codon 312 and 751 of XPD are correlated with DNA-adducts levels, p53 gene mutation, and cancers risk (88,94,(98)(99)(100). In a hospital-based case-control study in Guangxi (39), we found that the variant XPD codon 751 genotypes (namely Lys/Gln and Gln/Gln) detected by TaqMan-MGB PCR was significantly different between controls (26.3% and 8.6% for Lys/Gln and Gln/Gln, respectively) and HCC cases (35.9% and 20.1% for Lys/Gln and Gln/Gln, respectively, P < 0.001).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Currently, however, genetic polymorphisms are promising, but still cannot completely identify individuals at higher cancer risk. Therefore, other factors that could affect adduct formation in vivo should be taken into account, like gender (Ryberg et al, 1994), body composition (Godschalk et al, 2002), diet (Palli et al, 2000) and DNA repair efficiency (Tang et al, 2002). Since the variation in adduct formation within or between individuals can be high, the question remains whether aromatic-DNA adduct levels in WBC can be applied to discriminate between individuals in various exposure or risk groups.…”
Section: Understanding Inter-and Intra-individual Variabilitymentioning
confidence: 99%